2023
DOI: 10.1029/2023jd039199
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Ozone Sensitivity to Urban Greening in Los Angeles Under Current Day and Future Anthropogenic Emissions Scenarios

Hannah L. Schlaerth,
Sam J. Silva,
Yun Li

Abstract: Cities are simultaneously implementing urban greening and reducing anthropogenic emissions to combat climate change, but these strategies can have complex and potentially counteracting effects on regional atmospheric chemistry. Urban greening can increase emissions of volatile organic compounds (BVOCs), while climate change mitigation strategies reduce co‐emitted pollutants like nitrogen oxides (NOx). The nonlinear relationship between ozone (O3) and BVOC and NOx concentrations makes it crucial to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The study evaluates the effects of UGS-BVOC and UGS-LUCC on MDA8 O3 concentrations in Guangzhou, both individually and in combination. The analysis reveals that the UGS-BVOC emissions alone (Figure 6 A) primarily affect urban areas, significantly increasing MDA8 O3 concentrations by 2.2-3.0 μg/m³ (+2.3-3.2%), which increment aligns with findings from Los Angeles, where Schlaerth et al, (2023) reported a contribution of 2.5 μg/m³ from UGS-BVOC to urban MDA8 O3 levels. In contrast, the sole impact of the UGS-LUCC this change also reduces the height of the urban canopy, diminishing its shading effects on solar radiation and paradoxically leading to higher temperatures in some regions.…”
Section: Impact Of Ugs-lucc and Ugs-bvoc On Ozone Concentrationssupporting
confidence: 80%
“…The study evaluates the effects of UGS-BVOC and UGS-LUCC on MDA8 O3 concentrations in Guangzhou, both individually and in combination. The analysis reveals that the UGS-BVOC emissions alone (Figure 6 A) primarily affect urban areas, significantly increasing MDA8 O3 concentrations by 2.2-3.0 μg/m³ (+2.3-3.2%), which increment aligns with findings from Los Angeles, where Schlaerth et al, (2023) reported a contribution of 2.5 μg/m³ from UGS-BVOC to urban MDA8 O3 levels. In contrast, the sole impact of the UGS-LUCC this change also reduces the height of the urban canopy, diminishing its shading effects on solar radiation and paradoxically leading to higher temperatures in some regions.…”
Section: Impact Of Ugs-lucc and Ugs-bvoc On Ozone Concentrationssupporting
confidence: 80%
“…The instantaneous DRF at the TOA is stronger in northern China than in the south (Figure 3), resulting from the disparity in surface albedo between the two regions (Figure S5 in Supporting Information ). The higher surface albedo in northern China compared to the south might be primarily due to larger snow cover and bare surfaces, such as the Gobi Desert (He et al., 2014; Schlaerth et al., 2023; Yan et al., 2021), especially in the winter months (Figure S5 in Supporting Information ). Surfaces with high albedo could reflect more solar radiation back to the atmosphere, enhancing the absorption of this reflected radiation by BC, which would induce a stronger positive IDRF and a weaker negative IDRF under the same aerosol loading conditions (W. Chen et al., 2021; Ocko et al., 2012; Zhuang et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that global warming may increase the frequency and intensities of heatwaves and urban heat island effects, , such that the impacts of temperature-dependent AVOC emissions on ozone may become more pronounced in the future. Other underestimated or unrepresented natural and anthropogenic emissions of ozone precursors, such as soil-NO x emissions and emissions associated with urban greening practices, may also cause complex ozone-temperature sensitivities. These linkages between air pollution and meteorology should be considered in our projection of long-term air quality trends to better inform the long-term emission reduction goals.…”
Section: Uncertainties and Implications For Regional Air Quality Mana...mentioning
confidence: 99%